Protective Effects of Carvacrol against Oxidative Stress Induced by Chronic Stress in Rat’s Brain, Liver, and Kidney - Saeed Samarghandian; Tahereh Farkhondeh; Fariborz Samini; Abasalt Borji (Biochemistry Research International)
Restraint stress may be associated with elevated free radicals, and thus, chronic exposure to oxidative stress may cause tissue damage. Several studies have reported that carvacrol (CAR) has a protective effect against oxidative stress. The present study was designed to investigate the protective effects of CAR on restraint stress induced oxidative stress damage in the brain, liver, and kidney. For chronic restraint stress, rats were kept in the restrainers for 6 h every day, for 21 consecutive days. The animals received systemic administrations of CAR daily for 21 days. To evaluate the changes of the oxidative stress parameters following restraint stress, the levels of malondialdehyde (MDA), reduced glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GR), and catalase (CAT) activities were measured in the brain, liver, and kidney. In the stressed animals that received vehicle, the MDA level was significantly higher (P<0.001) and the levels of GSH and antioxidant enzymes were significantly lower than the nonstressed animals (P<0.001). CAR ameliorated the changes in the stressed animals as compared with the control group (P<0.001). This study indicates that CAR can prevent restraint stress induced oxidative damage.